A importância do microcrédito para os empreendedores: um estudo com os grupos solidários de Fortaleza /CE - Santos, Luciana Guedes (2010)
This study aims to understand the changes in the improvement of economic and social conditions of small entrepreneurs who participate in solidarity groups linked to the Non-Governmental Organization (NGO) "X" in Fortaleza city, Ceará, through the use of productive-guided microcredit. It is come a research in exploratory and descriptive nature, with a quantitative and qualitative approach. Data were collected from the small entrepreneurs by applying a questionnaire, as well as through structured interviews with group leaders. They were worked on issues relating to income generation, employment generation, housing and health conditions, dietary pattern and leisure activities of small entrepreneurs and their families before and after the union to solidarity groups and use of productive-guided microcredit. The research showed that the use of microcredit has interfered with social and economic life of these small entrepreneurs, generating positive effects